Knowledge Management Guideline of Agricultural Process Innovation for Elderly’s Wellbeing in Krainok Elders School, Sukhothai Province - Wathinputthiporn, Donchida; Srinoul, Nichaphorn (Area Based Development Research Journal, 2021)
The elderly in Krainok subdistrict, Sukhothai province had pesticide contaminated in the blood, could not access safe food, and had physical limitations in framing. So this participatory action research aims to develop knowledge management guidelines to search for agricultural process innovation the wellbeing for the elderly at the Krainok Elders School by using the SECI Model knowledge management framework, consists of 4 steps as follows: 1) the socialization step was to search for network partners jointly, to study and analyze data on agricultural forms and suitable technologies for the elderly; 2) the externalization step was to study the guidelines of knowledge management of agricultural process innovation for the elder’s people’s wellbeing into manual, curriculum, demonstration plots, and resource person; 3) the combination and internalization steps were to improve the potential of the elderly according to knowledge management approaches by curriculum and supportive resources developed; 4) Assessment step was to evaluate and lesson learns. The learning outcomes from the curriculum revealed that the elderly was inspired to do by the Good Agricultural standard. They had learnt and understood in safety production, marketing and sharing knowledge with the elderly in neighboring sub-districts. The results by self-assessment were as follows; overall of the elderly’s opinions and cognition to the agricultural innovation in 4 dimensions at the highest level; in health, mentality, social, and intellectual. In addition, the research found approximately 17.58% grew their own vegetables after participating in the project. They could reduce household expenses about 812.20 baht/month/household. The results of lessons learned found that older people could access to more safe food, learn to work in suitable plant plots for their own physical condition and safe farming. They could exchange and learn together, reduce stress, and proud to be as a giver of safety food to their community.